Analysis of the educational resources used in the course Fundamentals of Informatics in the face of the COVID-19 pandemic - Hernández Ruiz, Irene (2022)
Technology brought several advancements to the Educational area in the past few years, including digital resources such as Open Educational Resources (OER). However, higher demand associated with the lack of platforms that facilitate the search and sharing of these resources is an impeditive factor, often causing the devaluation and loss of these materials. This article presents ReaCloud, a digital repository designed to index OERs, improve the usability of adding OERs, and aligned with Brazilian standards for k-12 education.